1-D and 2-D Monte Carlo simulations for analysis of CPV module characteristics including the acceptance angle impacted by assembly errors. (1st May 2017) - Araki, Kenji; Nagai, Hirokazu; Herrero, Rebeca; Antón, Ignacio; Sala, Gabriel; Lee, Kan-Hua; Yamaguchi, Masafumi
Highlights: Impact of the component variance and assembly error in the CPV modules was quantitatively analyzed. The 2-D Monte Carlo method can predict the acceptance angle of the CPV modules. The measured behaviors of CPV modules impacted by assembly errors were closed to the predicted. Design rules on the control of component variance and assembly tolerant control were proposed. Abstract: CPV (Concentrator photovoltaic) requires accuracy in optical alignment. Optical misalignment in the module was measured and analyzed. Such information was useful to identify assembly problems and improved module performance. 1-D and 2-D Monte Carlo simulations were developed to analyze the impact of alignment errors by assembly errors. The 1-D simulation was useful to anticipate the power output of the module, whereas 2-D was for acceptance angle. The 2-D model showed that the gap from Pmp -based acceptance angle ( Pmp : Power at the maximum power point) from that of Isc -based ( Isc : Short-circuit current) was a function of deviation of assembles misalignment in the module. The rough rule for the acceptable assembles misalignment is that the standard deviation of the assemble misalignment will be less than 10% of acceptance angle of the optics, whereas that of power output of the single module is 20%. This fact implies that the inspection of the acceptance angle is highly recommended in the CPV module production.